Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1142/s0218202505000923
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Methods and Tools of Kinetic Theory Towards Modelling Complex Biological Systems

Abstract: This paper develops a variety of mathematical tools to model the dynamics of large systems of interacting cells. Interactions are ruled not only by laws of classical mechanics, but also by some biological functions. The mathematical approach is the one of kinetic theory and non-equilibrium statistical mechanics. The paper deals both with the derivation of evolution equations and with the design of specific models consistent with the above-mentioned mathematical framework. Various hints for research perspective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
58
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(58 citation statements)
references
References 13 publications
0
58
0
Order By: Relevance
“…Considering the case of nonlocal interactions is important when dealing with biological systems: the dialogue between cells suggests to consider long range interactions as already documented in the paper [10]. The same issues are dealt with in the paper [32], where it is shown that modelling nonlocal interactions has a remarkable influence on the description of macroscopic biological phenomena.…”
Section: Introductionmentioning
confidence: 98%
“…Considering the case of nonlocal interactions is important when dealing with biological systems: the dialogue between cells suggests to consider long range interactions as already documented in the paper [10]. The same issues are dealt with in the paper [32], where it is shown that modelling nonlocal interactions has a remarkable influence on the description of macroscopic biological phenomena.…”
Section: Introductionmentioning
confidence: 98%
“…Therefore the contents refer to methodological aspects, while a specific application is presented in [4], which deals with the immune competition between tumor and immune cells. The study of methods of the mathematical kinetic theory for modelling multicellular systems with application to the immune competition is documented in several recent papers; see [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The analysis refers to class of models proposed in [1]-further developed in [2]-which consists of a system of nonlinear integro-differential equations with quadratic type nonlinearity. The structure is somewhat similar to that of classical models of the mathematical kinetic theory [3].…”
Section: Introductionmentioning
confidence: 99%